The complex dependence of non-enzymatic browning development on processing conditions in maize snacks - Rolandelli, Guido; Favre, Leonardo Cristian; Mshicileli, Ndumiso; Vhangani, Lusani Norah; Farroni, Abel Eduardo; Van Wyk, Jessy; Buera, María del Pilar (Elsevier, 2021)
The complex dependence of non-enzymatic browning development on processing conditions was analyzed in the production of maize snacks. The influence of the amount of water added to maize flour, toasting time, and toasting temperature on final water contents, HMF formation and CIELAB color parameters was evaluated by Response Surface Methodology. While L* values decreased continuously with increasing toasting temperature, the variables a* and b* showed maximum values at intermediate studied ranges of temperature and water contents, which is related to the complex interactions of the variables water content and temperature. The formation of HMF, as a marker of non-enzymatic browning reactions, was favored by low water contents and its concentration correlated with lower L* and b* but higher a* values. The optimum levels of toasting time, toasting temperature, and water addition for minimizing HMF concentration at which the snacks presented adequate color characteristics were determined. Finally, correlations between L*, b* and HMF were mathematically established to predict heat damage using these fast and non-destructive indicators to assure adequate processing and storage conditions.